Diagnosis and Management of Endocrine Disorders in Interventional Radiology - Yu, Hyeon; Burke, Charles T.; Commander, Clayton W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a comprehensive guide for selective venous sampling procedures and the role of interventional radiologists in the care and treatment of patients with endocrine disorders. Selective venous sampling is a minimally invasive interventional procedure that interventional radiologists perform to localize sites of abnormal hormone secretion. As these various venous samplings are increasingly performed worldwide, the collaboration between interventional radiology, endocrinology, surgical endocrinology, surgical oncology, neurosurgery, and gynecology teams is essential. With limited literature on the topic, this volume fills the gap with in-depth coverage of selective venous sampling alongside the pathophysiology, epidemiology, clinical diagnosis, as well as medical, surgical, and interventional management of endocrine disorders. The book is divided into five parts: Clinical, Laboratory, and Radiological Diagnosis of Endocrine Disorders; Selective Venous Sampling in Interventional Radiology; Medical Treatment of Endocrine Disorders; Surgical Treatment of Endocrine Disorders; Interventional Treatment of Endocrine Disorders. Throughout these parts, endocrine disorders that require venous sampling are covered in depth: primary aldosteronism, primary hyperparathyroidism, Cushing$1 (Bs disease, hormone-secreting pancreatic adenomas, and androgen-secreting ovarian tumors. There is additionally an emerging role for interventional management in thyroid gland disorders, which is covered here. This is an ideal guide for interventional radiologists caring for patients with endocrine disorders, as well as endocrinologists, endocrine surgeons, surgical oncologists, otolaryngologists, neurosurgeons, gynecologists, and nephrologists.s
PART 1. Clinical & Laboratory Diagnosis of Endocrine Disorders -- Clinical Evaluation -- Laboratory Evaluation (Clinical Chemistry and Pathology) -- PART 2. Selective Venous Sampling in Interventional Radiology -- Primary Aldosteronism -- Hyperparathyroidism -- Hyperandrogenism (Hirsutism) -- Cushing$1 (Bs Disease (ACTH-producing Pituitary Adenoma) -- Pancreatic Islet tumors (Insulinoma & Gastrinoma) -- PART 3: Medical Treatment of Endocrine Disorders -- Medical Treatment of Endocrine Disorders -- PART 4: Surgical Treatment of Endocrine Disorders -- Surgical Treatment of Primary aldosteronism -- Surgical Treatment of Hyperparathyroidism -- Surgical Treatment of Hyperandrogenism (Hirsutism) -- Surgical Treatment of Pancreatic islet cell tumors (insulinoma & gastrinoma) -- Surgical Treatment of Cushing$1 (Bs disease (ACTH-producing pituitary tumor) -- PART 5: Interventional Treatment of Endocrine Disorders -- Interventional Treatment of Adrenal Adenoma with Primary Aldosteronism -- Interventional Treatment of Parathyroid Adenoma with Primary Hyperparathyroidism -- Interventional Treatment of Thyroid Nodule with Hyperthyroidism -- Interventional Treatment of Pancreatic Islet Cell Transplantation -- Interventional Treatment of Hepatic Endocrine Tumor. .s
Keywords: Radiology; Radiology; Endocrine System Diseases; Radiology, Interventional